Analysis of Perwali No. 16 of 2022 Policy in Reducing Plastic Bag Usage in Surabaya City - Muhamad Tri Samudera (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study analyzes the implementation of Surabaya Mayor Regulation No. 16 of 2022, aimed at reducing single-use plastic bags. Enforced since April 9, 2022, the policy targets shopping centers, supermarkets, traditional markets, and restaurants. Using a descriptive quantitative approach, data were gathered through surveys of 25 business actors and 40 residents during an internship program with the Surabaya City Government, supported by secondary data from the Environmental Agency and the 2021–2026 RPJMD document. Findings show that while 83% of business actors are aware of the regulation, 72% still use plastic bags due to economic concerns, fear of declining sales, and customer complaints. On the other hand, 89% of residents prefer to bring their own shopping bags, indicating high environmental awareness. The main challenges lie in limited enforcement and the lack of affordable eco-friendly alternatives, especially in traditional markets. The study recommends stronger public outreach, tax incentives for businesses switching to eco-friendly bags, stricter enforcement, continued education on plastic waste impacts, and greater availability of affordable alternatives to accelerate the shift toward sustainable bag usage in Surabaya.